Job Evaluation: The role of management and unions in four countries - C. J. Cogill (South African Journal of Business Management, 1984)
The development of job evaluation practice is examined in Britain, America, the Netherlands and South Africa. The role of management and unions is traced to highlight important content, process and value Issues. The initial phases of development of job evaluation arise out of attempts by major public or private bodies to rationalize chaotic wage rates. Job evaluation schemes are often implemented by management together with significant increases in wages and salaries. Unions invariably welcome the increases and do not question the rationality of the underlying plans. When, however, increases are no longer as large and when unions become more critical and knowledgeable they question the underlying tenets and processes. Further impetus to the development of job evaluation practice is gained when equal pay legislation or intent is introduced. Questioning of the plans and processes often leads to union involvement and joint management/labour committees devising plans and evaluating jobs. On the basis of this simple developmental model it is hypothesized that organizations in South Africa are entering the critical questioning phase and that considerably more attention will be focussed on union involvement in job evaluation processes.
Keywords: 650